Finite Element Analysis of Compressive Strength in Matoa and Ironwood: A Sustainable Perspective - Eko Tavip Maryanto; Rezza Ruzuqi (Chemical and Materials Sciences: Developments and Innovations Vol. 6, 2024)
Composite materials, which consist of a multi-phase system of reinforcing materials and matrix materials, can be classified into synthetic and natural composites. Wood, a natural composite material, includes both reinforcement and matrix components. This study focuses on the compressive mechanical strength of matoa wood (Pometia vinnata) and ironwood (Eusideroxylon zwageri). Known for its good mechanical properties, matoa wood is compared with ironwood to support its potential use as an environmentally friendly material for house foundation piles. The Finite Element Method (FEM), a numerical analysis technique, is employed to evaluate the compressive strength of these natural composite materials. A 2D FEM analysis was conducted to determine the compressive strength of matoa and ironwood using Ansys software. Three different finite element numbers were used in the analysis. The results for matoa wood were A1 = 6.07e-07 MPa, A2 = 1.11e-06 MPa, and A3 = 2.09e-06 MPa, while for ironwood, the results were B1 = 1.17e-06 MPa, B2 = 2.13e-06 MPa, and B3 = 4.02e-06 MPa. These findings indicate that ironwood has a higher resistance to mechanical compression compared to matoa wood. Despite ironwood's superior mechanical properties, matoa wood offers significant environmental benefits. Matoa trees are easy to cultivate and their roots do not damage surrounding plants, making them an effective and efficient environmentally friendly option. This study highlights the potential of matoa wood as a sustainable material in construction applications, providing both mechanical and ecological advantages.